Investigation of the Azorean Camellia sinensis Processing Conditions to Maximize the Theaflavin 3,3'-di-O-Gallate Content as a Potential Antiviral Compound - Paiva, Lisete (2022)
ABSTRACT: The molecular constituents of Camellia sinensis, in particular epigallocatechin‐3‐O‐gallate (EGCG) and, more remarkably, the galloylated theaflavins, mainly theaflavin‐3,3′‐di‐O‐gallate (TF‐3,3′‐DG), have been reported to inhibit SARS‐CoV‐2 3‐chymotrypsin‐like protease (3CLpro), an enzyme required for the cleavage of its polyproteins, to produce vital individual functional proteins for viral cell replication. Our results for total catechin content revealed the values of 174.72, 200.90, and 211.75 mg/g dry weight (DW) in spring, and the values of 183.59, 191.36, and 215.09 mg/g DW in summer, for tea plantation zones 1, 2, and 3, respectively. For the TF‐3,3′‐DG content, the values of 2.68, 1.13, and 3.72 mg/g DW were observed in spring, and the values of 3.78, 2.06, and 8.91 mg/g DW in summer for zones 1, 2, and 3, respectively. In the same zone, different contents of TF‐3,3′‐DG were observed across plucking months of April, June, and August, with values of 1.13, 2.77, and 4.18 mg/g DW, respectively, showing higher values in summer. Different values of TF‐3,3′‐DG contents were also observed in the same tea plantation zone but from different plant parts, revealing higher values in the bud and the first and second leaves (3.62 mg/g DW) and lower values in the third and fourth leaves (1.14 mg/g DW). The TF‐3,3′‐DG content increased from 3.31 to 4.98 mg/g DW with increased fermentation time from 1 to 3 h, respectively, and increased for lower temperature and longer fermentation time. The aim of this study was to investigate the processing conditions that lead to maximum TF‐3,3′‐DG content and, given its potential impact as an inhibitor of the 3CLpro enzyme, to create a novel antiviral Azorean black tea.